2006
DOI: 10.1161/01.atv.0000204634.26163.a7
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ Gene Transfer Sustains Apoptosis, Inhibits Vascular Smooth Muscle Cell Proliferation, and Reduces Neointima Formation After Balloon Injury in Rats

Abstract: Objective-There is still debate as to whether antiatherosclerotic effect of PPAR␥ ligands is dependant on PPAR␥ gene itself or some other pathway. Methods and Results-To investigate the effect of PPAR␥ gene modulation on neointima formation after balloon injury, we delivered adenoviral vectors expressing the wild-type (WT) dominant negative (DN) PPAR␥, or a control gene (␤-galactosidase [BG]) into carotid artery after balloon injury in rosiglitazone (a PPAR␥ ligand)-treated (Rϩ) (3 mg/kg/d) and nontreated (RϪ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 54 publications
(54 reference statements)
3
52
0
Order By: Relevance
“…However, numerexpressed dominant-negative PPARγ in endothelium demonstrated the development of endothelial dysfunction in response to a high-fat diet [22]. PPARγ ligands have also been reported to reduce intimal and medial complex thickening in carotid arteries and in-stent restenosis after coronary intervention in both diabetic and non-diabetic patients [23] as well as neointima formation after balloon injury in rats [24] and in-stent restenosis in atherosclerotic rabbits [25]. In order to examine the direct effects of PPARγ ligands on endothelial gene expression, we performed DNA microarray analyses.…”
Section: Resultsmentioning
confidence: 99%
“…However, numerexpressed dominant-negative PPARγ in endothelium demonstrated the development of endothelial dysfunction in response to a high-fat diet [22]. PPARγ ligands have also been reported to reduce intimal and medial complex thickening in carotid arteries and in-stent restenosis after coronary intervention in both diabetic and non-diabetic patients [23] as well as neointima formation after balloon injury in rats [24] and in-stent restenosis in atherosclerotic rabbits [25]. In order to examine the direct effects of PPARγ ligands on endothelial gene expression, we performed DNA microarray analyses.…”
Section: Resultsmentioning
confidence: 99%
“…61 Rosiglitazone also inhibits c-fos gene expression and dominant-negative PPAR-␥ gene transfer abolishes this effect in cultured VSMCs treated with basic FGF. 70 Eukaryotic initiation factor 4E-binding protein (4E-BP)1 and SHIP2 (Src homology 2-containing inositol phosphatase 2) are also likely to mediate the growth inhibition of PPAR-␥ agonists. 71 Both 15d-PGJ2 and rosiglitazone decrease the phosphorylation of 4E-BP1 and SHIP2 that is elevated by Ang II in VSMCs when they inhibit the DNA synthesis in vitro.…”
Section: Ppar-␥ Activation/inactivation In Vsmcsmentioning
confidence: 99%
“…55 PPAR-␥ gene transfer into VSMCs induces apoptosis while inhibiting proliferation and migration in vitro and in vivo. 70 This indicates that VSMC apoptosis may be antiatherogenic by counteracting proliferation and migration. PPAR-␥ agonists have been shown to induce apoptosis of VSMCs from humans or rodents.…”
Section: Ppar-␥ Activation/inactivation In Vsmcsmentioning
confidence: 99%
“…It is reported that after carotid arteries injury, VSMCs proliferation in the intima was highest at the 7th day postinjury, whereas the rate of apoptosis in VSMCs was unchanged and lower than 1%, suggesting an insufficient rate of cell apoptosis concomitant with intimal hyperplasia (Kamenz et al, 2000). It has been demonstrated that increasing VSMCs apoptosis could decrease neointimal hyperplasia in vivo (Lim et al, 2006). Gax overexpression inhibits the proliferation of hypoxia-induced pulmonary arterial smooth muscle cells (PASMCs) and promotes apoptosis in the PASMCs (Xia et al, 2011).…”
Section: Discussionmentioning
confidence: 99%